Efficacy of Ultrasound‐Guided Needle Biopsy in the Diagnosis of Kikuchi‐Fujimoto Disease. (1st October 2020) - Park, Sang Gyu; Koo, Hye Ryoung; Jang, Kiseok; Myung, Jae Kyung; Song, Chang Myeon; Ji, Yong Bae; Park, Jeong Seon; Tae, Kyung
Abstract : Objectives/Hypothesis: Ultrasound‐guided fine‐needle aspiration cytology (US‐FNAC) is a well‐established procedure performed to establish the diagnosis of Kikuchi‐Fujimoto disease (KFD). Ultrasound‐guided core needle biopsy (US‐CNB) is an alternative diagnostic tool for KFD. However, the efficacy of US‐CNB is not well evaluated. This study aimed to evaluate the efficacy of US‐CNB and compare it with that of US‐FNAC in the diagnosis of KFD. Study Design: Retrospective cohort study. Methods: We analyzed 170 patients who were diagnosed with KFD between January 2009 and May 2019. US‐FNAC, US‐CNB, and excisional biopsy were performed in 47, 114, and 9 patients, respectively. Diagnostic accuracies of US‐FNAC and US‐CNB were analyzed and compared. Results: Of the 170 patients, 45 and 125 were men and women, respectively. The mean age was 26.9 ± 9.1 years. The most common symptom was cervical lymphadenopathy, followed by fever, headache, and myalgia. The diagnosis of KFD was established primarily by US‐FNAC in 21 (44.7%) of the 47 patients, by US‐CNB in 109 (95.6%) of the 114 patients, and by excisional biopsy in all 9 patients. There was no specific major complication related to US‐FNAC and US‐CNB. Conclusion: US‐CNB can be considered safe and effective and used as the primary modality for the pathological diagnosis of KFD. Level of Evidence: 4. Laryngoscope, 131:E1519–E1523, 2021